The genesis of indigenous Malay worldview as manifested by the built environment : qualities in the indigenous Malay worldview - Azmin, Aida Kesuma (IIUM Press, 2011)
This chapter attempts to explore more deeply into the genesis of the indigenous arts and architecture of the Malay society, in order to decipher the origin of the community's cultural worldview and its significance on its dwelling designs and living environments. The Malay community is one who practices the religion of Islam, while simultaneously, also sustains its cultural and cosmological traditions that are parallel with the teachings of Islam. However, in tracking the evolution and development of indigenous Malay worldviews, it is imperative to recognise that the indigenous intellectual framework is divided into three stages of development, i.e. from animism! shamanism era, to Hindu-Buddhism dominion and finally to Islam. The reader should also be able to notice the existence of boundary among these three types of worldvie\vs. The topic stresses the importance of recognising the significance of the religion, tradition and cosmology as deep-rooted embedded forces responsible for producing indigenous and sustainable representation of domestic architecture within the society. Symbolism and meaning in the architecture of indigenous dwellings are vital for the Malay community to decipher the relationship between Man and God, Man and Nature. Symbolic representations of the traditional Malay arts and crafts illustrate the existence of aesthetics, quality and values in this workmanship, which are highly significant to the ".ray the Malay people behave and lead their lives. How people interpret their worldviews are imperative in deciphering the reasons i.e. the meaning behind the manifested forms of dwellings in a variety of patterns. Through this understanding, only then can one produce contemporary dwelling design closer to the context ofhome.